Black tea aroma formation during the fermentation period. (16th April 2022) - Chen, Qincao; Zhu, Yin; Liu, Yafang; Liu, Yang; Dong, Chunwang; Lin, Zhi; Teng, Jie
Highlights: Dynamic variations of volatiles and their precursors in fermentation were studied. Strong fermentation activities also occurred during the rolling step. GBVs (especially primeverosides) were greatly hydrolyzed during fermentation. Fermentation largely upgrades the ratio of sweet/floral scent to green scent. AADVs and CDVs promoted formation of sweet/floral odor more than VTs. Abstract: The present study aimed to systematically investigate black tea aroma formation during the fermentation period. In total, 158 volatile compounds were identified. Of these, most amino acid-derived volatiles (AADVs) and carotenoid-derived volatiles (CDVs) showed significant increases, while fatty acid-derived volatiles (FADVs) and volatile terpenoids (VTs) displayed diverse changes during the fermentation period. During this time, fatty acids, amino acids, carotenoids, and glycosidically bound volatiles (GBVs, especially primeverosides) were found to degrade to form aroma components. Further, equivalent quantification of aroma showed that the intensity of green scent was notably decreased, while the intensities of sweet and floral/fruity scents were greatly increased and gradually dominated the aroma of tea leaves. AADVs and CDVs were shown to make greater contributions to the formation of sweet and floral/fruity scents than VTs. Our study provides a detailed characterization of the formation of sweet and floral/fruity aromas in black tea during the fermentation period.